2021
DOI: 10.1108/jkm-10-2020-0800
|View full text |Cite
|
Sign up to set email alerts
|

Top management support and knowledge sharing: the strategic role of affiliation and trust in academic environment

Abstract: Purpose Knowledge sharing, the most important process in knowledge management, enables knowledge-intensive organizations to foster innovations and to gain competitiveness. Universities, the best contemporary embodiments of knowledge-intensive organizations, nowadays face fiercer competition in the changing world. Knowledge sharing is the key for academic departments to gain competitive advantages through innovation. However, limited studies examined the relationships between top management support, knowledge s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 78 publications
0
27
0
5
Order By: Relevance
“…The study noted a positive effect of ABT on KS and EC ( H1–H3 ). The relationship between trust and KS is well documented (Lo et al , 2021; Yu and Takahashi, 2021). These studies have suggested that employees are more willing to learn, communicate and deliver knowledge where there is higher level of trust (Hsu and Chang, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The study noted a positive effect of ABT on KS and EC ( H1–H3 ). The relationship between trust and KS is well documented (Lo et al , 2021; Yu and Takahashi, 2021). These studies have suggested that employees are more willing to learn, communicate and deliver knowledge where there is higher level of trust (Hsu and Chang, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Kmieciak (2020) identified horizontal and vertical trust, whereas Swift and Hwang (2013) noted cognitive-based trust as the predictors of KS. Still, literature on the association between ABT and KS is scant (Lo et al , 2021; Lee, 2021). The findings of this study confirms that individuals with ABT are more likely to exhibit KS behaviors, because ABT is based on emotional connection between employees.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Більшість людей як носії знань потребують створення корпоративної культури, яка би спонукала їх обмінюватися знаннями, що і є організаційним складником системи управління знаннями. Зарубіжні дослідники акцентують увагу на ролі і важливості підтримки топ-менеджментом університету процесу обміну знаннями -найважливішого процесу в управлінні знаннями, що дає можливість наукоємним організаціям сприяти інноваціям і досягти конкурентоспроможності (Lo et al, 2021), а також вказують на важливість ролі організаційного клімату в управлінні обміном знаннями між науковцями закладів вищої освіти (Al-Kurdi et al, 2020).…”
Section: управління знаннями та інформацією як чинник забезпечення якості вищої освіти: зарубіжний досвідunclassified